-2y+9=3

Simple and best practice solution for -2y+9=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2y+9=3 equation:


Simplifying
-2y + 9 = 3

Reorder the terms:
9 + -2y = 3

Solving
9 + -2y = 3

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + -2y = 3 + -9

Combine like terms: 9 + -9 = 0
0 + -2y = 3 + -9
-2y = 3 + -9

Combine like terms: 3 + -9 = -6
-2y = -6

Divide each side by '-2'.
y = 3

Simplifying
y = 3

See similar equations:

| (2c-5d)3=x | | 3(x+5)-12=9+3x-6 | | graphY-9=0 | | 9*320=16*a | | Y+1=3(x-3) | | B+12=42 | | 9*a=16*320 | | -5x+2(-x+9)=-31 | | K+15=0 | | 557.50+x=3482.50 | | c=346-856 | | 7a+10=2a+10 | | 48.5=x*97 | | 4k^2-8k-3=3-5k^2 | | w-13+2w=131 | | 5x+4x-6+8-6x= | | 0.7n-1.5+7.3k=14.5 | | 3-4x=-8x+12 | | F(x)=x^2-7x+15 | | 15x-1=5x+13 | | 0=5x^2+5x-30 | | y=3x^4-12e^2x^2+12e^4 | | x^2=1056 | | r+7=-9 | | 19u+18u+8u=180 | | -5x+2(-x+9)=31 | | z^2-5z=30 | | -6-5a=-(-2+4a)-8 | | -15=x/2-3 | | 2/5-5 | | N+7=9+18 | | (X+8)=(2x-3) |

Equations solver categories